Syn for sagn. Tre fotografiske dokumentationsprojekter, 1895-1927 - Nyvang, Caroline (Tidsskrift for kulturforskning, 2013)
Picturing the Past - Three Photographical Projects, 1895-1927 This article analyses the use of photography in Danish folkloristic documentation of immaterial culture. In particular, it focuses on the work of Axel Olrik (1864-1917), the first president of the Danish Folklore Archives and a representative of the early folkloristic movement, and his engagement in three different photographical projects during the years 1895-1927. Through a study of the actual pictures as well as readings of Olrik's personal letters, applications for funding, and academic writings, two main arguments for the use of photography are identified: one line of argumentation pertains to the potential of photography as a conservatory technology; another series of reasons promotes photographs as a particularly well-suited medium for conveying the past in a holistic way. Furthermore, the article shows how these arguments hinge on a coalescence of time and space, comparable to that of concurrent ethnographic photography.